THE INFLUENCE OF USING EDUCAPLAY TOWARD STUDENTS’ VOCABULARY MASTERY AT SMK MUHAMMADIYAH 1 METRO - Rini Indriyani; Bambang Eko Siagiyanto; Fitri Palupi Kusumawati (English Education Study Program, 2025)
This study aims to find out whether Educaplay has an effect and significant effect toward students’ vocabulary mastery of eleventh grade students at SMK Muhammadiyah 1 Metro. This study using quasi-experimental research with experimental and control group. The subject of this study was the eleventh grade of TJKT students at SMK Muhammadiyah 1 Metro. The population of this research was 40 students which consist of 20 students of TJKT 1 as experimental group and 20 students of TJKT 2 as control class. The data were taken by giving vocabulary test which consists of multiple choice. The tests were divided into two tests: pre-test and post-test for both experimental and control groups. The result showed an effect and significant toward students vocabulary mastery, based on the result of hypothesis testing for the first hypothesis the result of significant value is <0.001<0.05, it means that Ha accepted meanwhile Ho rejected. The for he second hypothesis the result of significant value is 0.045<0.05, therefore it can be conclude that Ha is accepted and Ho rejected. The conclusion is Educaplay gave effect and significant effect toward students vocabulary mastery.